1998
DOI: 10.1071/pp97015
|View full text |Cite
|
Sign up to set email alerts
|

Responses to water stress of enzyme activities and metabolite levels in relation to sucrose and starch synthesis, the Calvin cycle and the C4 pathway in sugarcane (Saccharum sp.) leaves

Abstract: During a slowly induced water stress, almost all measured activities of enzymes, including the important enzymes associated with the Calvin cycle, the C4 pathway, and sucrose and starch synthesis, and the pool sizes of metabolites, including hexose phosphates, 3-phosphoglycerate, triose phosphates, malate, pyruvate and PEP, in leaves of sugarcane (Saccharum sp. cv. NiF4) were not or only moderately reduced by mild water stress (above –0.9 MPa leaf water potential (Ψw)), and the magnitudes of reductions in thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…Significant increase in Ci for the WS plants on sand soil (Fig. 2c) between 20 and 25 days in 2009 or from 10-17 days in 2010 after initiating the WS treatment suggested that under severe water stress, decreased leaf Pn was mainly caused by non-stomatal limitation, such as photoassimilate enzyme activities (Du et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Significant increase in Ci for the WS plants on sand soil (Fig. 2c) between 20 and 25 days in 2009 or from 10-17 days in 2010 after initiating the WS treatment suggested that under severe water stress, decreased leaf Pn was mainly caused by non-stomatal limitation, such as photoassimilate enzyme activities (Du et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Determinations of metabolites and carbohydrates Triose-P, glucose-6-phosphate, glucose-1-phosphate, fructose-6-phosphate and FBP were extracted and determined as described earlier (Du et al, 1998). Sucrose, glucose, fructose and starch were extracted as before (Du et al, 1998), and determined photometrically using a modified enzymatic method Qones et al, 1977). The assay mixture ( 1.0 mL) contained 100 mM imidazo1-HC1 of pH 6.9, 0.5 mM NADP, 1.0 mM ATP, 5.0 mM MgC1 2 , 2 units of glucose-6-phosphate dehydrogenase and 20 J1.…”
Section: Extraction and Assays Of Enzymesmentioning
confidence: 99%
“…The extraction and assays of SPS, cytosolic FBPase, UDPG-PPase and ADPG-PPase were conducted as described earlier (Du et al, 1998), with SPS activity measured in an assay mixture without inhibitor orthophosphate.…”
Section: Extraction and Assays Of Enzymesmentioning
confidence: 99%
“…The extraction and determinations of the metabolites were carried out as described previously (Du et al, 1998). Figure IA shows the diurnal patterns of PAR of sunlight and CER in sugarcane leaves.…”
Section: Determinations Of Enzyme Activities and Metabolite Contentsmentioning
confidence: 99%